HISTORY OF WATER RESOURCES DEVELOPMENT AND WATER RESOURCES MANAGEMENT IN THAILAND - Varitwuttikul, Khemika; Tana, Supasit; Wannasubchae, Supattra; Pampasit, Rudklaw (PEOPLE: International Journal of Social Sciences, 2017)
This article is the study on "the evolutionary development of water resources in Thailand." It drew mainly on document research and data analysis using content-based analysis and data interpretation gathered from research document, along with descriptive analysis. The findings of this study revealed that the evolutionary development of water resources and water resources management in Thailand can be divided into five periods of time: 1) Pre-historical Period, 2) Dvarawati Influence Period, 3) Khmer Influence Period, 4) Thon Buri Period, and 5) Rattanakosin Period until now. Based on this research study, the researchers suggest that this article can be used to compare the social geography of the basin that influences water resources management policies in Thailand through the description with the related theory in order to clearly understand the context of the community and be able to access and develop water resources management according to geosocial base sustainably